Biohybrid and Bioinspired Magnetic Microswimmers. Issue 29 (31st May 2018) - Bente, Klaas; Codutti, Agnese; Bachmann, Felix; Faivre, Damien
Abstract: Many motile microorganisms swim and navigate in chemically and mechanically complex environments. These organisms can be functionalized and directly used for applications (biohybrid approach), but also inspire designs for fully synthetic microbots. The most promising designs of biohybrids and bioinspired microswimmers include one or several magnetic components, which lead to sustainable propulsion mechanisms and external controllability. This Review addresses such magnetic microswimmers, which are often studied in view of certain applications, mostly in the biomedical area, but also in the environmental field. First, propulsion systems at the microscale are reviewed and the magnetism of microswimmers is introduced. The review of the magnetic biohybrids and bioinspired microswimmers is structured gradually from mostly biological systems toward purely synthetic approaches. Finally, currently less explored parts of this field ranging from in situ imaging to swarm control are discussed. Abstract : Magnetic microswimmers are promising candidates for achieving microbot operation in medical or environmental scenarios. Their magnetic parts can be used to propel, guide, or image the devices during application. Here, current developments that include the biohybrid and the bioinspired approach are reviewed, and it is emphasized that complex environments, swarm control, and medical imaging need further investigation to achieve practical applications.